2021
DOI: 10.1021/acsnano.1c00968
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Metal/α-In2Se3/Si Crossbar Ferroelectric Semiconductor Junction

Abstract: A ferroelectric semiconductor junction is a promising two-terminal ferroelectric device for nonvolatile memory and neuromorphic computing applications. In this work, we propose and report the experimental demonstration of asymmetric metal/α-In2Se3/Si crossbar ferroelectric semiconductor junctions (c-FSJs). The depletion in doped Si is used to enhance the modulation of the effective Schottky barrier height through the ferroelectric polarization. A high-performance α-In2Se3 c-FSJ is achieved with a high on/off r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 28 publications
(54 reference statements)
1
44
0
Order By: Relevance
“…Si et al demonstrated a two-terminal ferroelectric semiconductor heterojunction device in crossbar formation (C-FSJ) using α-In 2 Se 3 and heavily-doped silicon. [133] The C-FSJ device achieved high on/off ratio > 10 4 at room temperature, retention > 10 4 s, and endurance > 10 6 cycles. The on/off ratio of the α-In 2 Se 3 asymmetric FSJs can be further enhanced to > 10 8 by introducing a metal/α-In 2 Se 3 /insulator/metal structure (Figure 13…”
Section: Memory Devicesmentioning
confidence: 91%
See 1 more Smart Citation
“…Si et al demonstrated a two-terminal ferroelectric semiconductor heterojunction device in crossbar formation (C-FSJ) using α-In 2 Se 3 and heavily-doped silicon. [133] The C-FSJ device achieved high on/off ratio > 10 4 at room temperature, retention > 10 4 s, and endurance > 10 6 cycles. The on/off ratio of the α-In 2 Se 3 asymmetric FSJs can be further enhanced to > 10 8 by introducing a metal/α-In 2 Se 3 /insulator/metal structure (Figure 13…”
Section: Memory Devicesmentioning
confidence: 91%
“…Si et al. demonstrated a two‐terminal ferroelectric semiconductor heterojunction device in crossbar formation (C‐FSJ) using α‐In 2 Se 3 and heavily‐doped silicon [133] . The C‐FSJ device achieved high on/off ratio >10 4 at room temperature, retention >10 4 s, and endurance >10 6 cycles.…”
Section: Device Applicationsmentioning
confidence: 99%
“…Compare with the symmetric “metal‐α In 2 Se 3 ‐metal” c‐FSJ, the depletion region in the p + Si electrode can modulate the height of the Schottky barrier through the polarization of the middle In 2 Se 3 . Through I – V characteristics, the asymmetric c‐FSJ exhibits a high on/off ratio of 10 4 at 0.2 V, which is significantly higher than that of the symmetric c‐FSJ 57,117 . In addition, α In 2 Se 3 ‐based asymmetric c‐FSJ has a strong ability of high‐temperature resistance.…”
Section: Electronic Devices Based On Ferroelectric 2d In2se3 For Data...mentioning
confidence: 97%
“…They could overcome the challenges faced by traditional ferroelectrics and have good applications in ultrahigh density and ultrafast speed memory, [ 30–33 ] optoelectronic multifunctional memories, [ 34,35 ] and ferroelectric semiconductor field‐effect transistors. [ 3,36,37 ] These materials usually have polar point group structure, such as 3m α‐In 2 Se 3 and m CuInP 2 S 6 . Yet, to introduce polar structure into otherwise nonpolar 2D materials to produce ferroelectricity, which enables more functionality and more flexible controllability, remains a challenge.…”
Section: Introductionmentioning
confidence: 99%